Nutrient status of phosphocompost and its effect on maize (Zea muys)-wheat (Triticum aestivum) cropping system as source of phosphorus in acid Alfisol of Ranchi, Jharkhand - MISHRA, B; SHARMA, A; ROY, N K; SHAHI, D K; LAL, J K (The Indian Journal of Agricultural Sciences, 2014)
An experiment was carried out during the rainy and winter seasons of 1992-96 to study the nutrient status of phosphocompost and its effect on maize (Zea mays L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system as source of P in acid Alfisol. A high-quality phosphocompost containing 4.01-6.5% rps was prepared in 1 m x 1 m x 1 m cemented pits from mixed plant materials, viz rice (Oryza sativa L.) straw, waterhyacinth [Eichhornia crassipes (C. martius) Solms-Laub], lantana (Lantana sp) and ipomoea (Ipomoea sp) leaves, in ,qual proportions reinforced with mussoorie rock phosphate in presence and absence offresh dung, soil and farmyard manpre in ratio of 8: 1 :0.5:0.5 on dry-weight basis. The quality of phospho compost was improved substantially in term ofincrcreased total P (1.75 to 2.87%), water-soluble P (280 to 470 mg/kg), citrate-solubleP (4 500 to 8 300mg/kg), total N (1.49 to 1.51 %) and mineral nitrogen (751 to 777 mg/kg). The prepared phosphocompost was compared favourably with 30 an9 60 kg pps basis with single superphosphate in a microplot field (10m2) during the rainy season of 1992-95 raising maize ('GS 2') and wheat ('RR 21') in winter season of 1992-93 to 1995-96 as test crops. The grain and straw yields of both maize and wheat were significantly superior in all the treatments containing P as phosphocompost and single superphosphate to the control. The highest yield (3 404 kg/ha maize grain and 2 481 kg/ha wheat grain) and increase (54.5 and 90.8% in maize and wheat respectively) over the control of maize and wheat were found in the treatment receiving N100 P60 as single superphosphate which was at par with treatment receiving Nloo P 60 as phosphocompost, while significantly superior to other treatments. The similar trend was observed for P uptake by both the test crops. The highest removal of P (32.68 kg/ha) by maize-wheat sequence was found in treatment N100 P60 as single superphosphate. The pH, organic carbon, available phosphorus and nitrogen were also influenced.